Community Service Entrepreneurship, Social Capability, and Sustainable Development: A Social Capital Perspective - ODESANMI, Akinola Festus; OLUSEGUN, Daniel Ilesanmi; BABATUNDE, Oluwole Samson; ASAMU, Festus Femi; KAYODE, Olumuyiwa Ebenezer; AROWOLO, Oluwatosin Tobi (Ilorin Journal of Education, 2025)
Community service entrepreneurship has emerged as social empowerment and sustainable development. At the intersection of community service and entrepreneurship lies a powerful catalyst for social change, offering both immediate support and long-term solutions. This approach highlights the strategies and practices that enable entrepreneurs to address complex social issues while advancing sustainable and equitable development. Rooted in Social Capital Theory, a sociological framework emphasising the importance of social networks, relationships, and norms, community service entrepreneurs play a crucial role in fostering personal and economic empowerment. It acts as an agent of collective action, driving social transformation and sustainability within communities. Additionally, these entrepreneurs contribute to shaping lifelong learning and nurturing knowledgeable, skilled, and empowered individuals who can enrich the social, economic, and cultural fabric of society. The paper concludes by recognising the pivotal role of community service entrepreneurship in promoting social empowerment, which governments and policymakers should prioritize and support by developing evidence-based frameworks, interventions, and policies so that societies can unleash their transformative potential.